TEACHING NARRATIVE TEXT THROUGH MIND MAPPING TECHNIQUE - Sri Yani; Ely Ezir; Irma Khoirot Daulay; M. Manugeren (JOURNAL OF LANGUAGE, 2022)
This research focused on teaching narrative text through mind mapping technique. The objectives of this research were to know and describe the process of teaching narrative writing using mind mapping. The data of this study were qualitative and quantitative. The qualitative data were obtained by observing the teaching-learning process during the implementation of the actions and interviewing the students and the collaborator about the implemented actions. The qualitative data were in the forms of field notes and interview transcripts. Meanwhile, the quantitative data were gained by assessing the students’ writing skill through the pre-test and the post-test. Therefore, the quantitative data were in the form of students’ writing scores in the pre-test and the post-test. The results of this study showed that the use of the mind mapping was effective to improve the students’ writing skill. The use of colorful pictures of mind mapping in the BKOF and MOT stages was effective to make the students more enthusiastic in the writing activities. The writers found that the student’s problems in writing were that the students were confused to develop their ideas because they did not have many vocabularies. Furthermore, the students had problems in matters of capitalization, punctuation, grammatical error, and organization. They also needed too much time to finish their writing.